Correction: Mechanism unravelling for highly efficient and selective 99TcO4− sequestration utilising crown ether based solvent system from nuclear liquid waste: experimental and computational investigations. Issue 10 (18th February 2022) - Patra, Kankan; Sengupta, Arijit; Boda, Anil; Ali, Musharaf; Mittal, V. K.; Valsala, T. P.; Kaushik, C. P.
Abstract : Correction for 'Mechanism unravelling for highly efficient and selective 99 TcO4 − sequestration utilising crown ether based solvent system from nuclear liquid waste: experimental and computational investigations' by Kankan Patra et al., RSC Adv., 2022, 12, 3216–3226. DOI: ; 10.1039/D1RA07738D .